Revolutionizing the Human Sciences: A Response to Wiebe - Josephson-Storm, Jason Ānanda (Method & theory in the study of religion, 2021)
Abstract In this short response, Storm challenges the limitations of the academic manifesto as a genre, criticizes tendencies toward a naive view of science in the study of religion, and gestures instead at the need for a comprehensive revolution in the human sciences.